Post-production Losses in Iodine Concentration of Salt Hamper the Control of Iodine Deficiency Disorders: A Case Study in Northern Ethiopia - Shawel, Dawit; Hagos, Seifu; Lachat, Carl K; Kimanya, Martin E; Kolsteren, Patrick (Journal of Health, Population and Nutrition, 2010)
Iodine is essential for good function of the thyroid, and its deficiency is of public-health importance in Ethiopia. Iodization of salt is an effective and sustainable strategy to prevent and control iodine deficiency in large populations. The effectiveness of salt-iodization programmes depends on the conservation of iodine concentration in salt at various stages of the supply-chain. The overall objective of the study was to assess the loss of iodine in salt from production to consumption and to estimate the proportion of adults, especially pregnant women, at risk of dietary iodine insufficiency. A cross-sectional study was conducted during February-April 2007 in northern Ethiopia. Iodine concentrations of salt samples from producers (n=41), retailers (n=7), and consumers (n=32) were determined using iodiometric titration. A risk assessment was conducted for dietary iodine insufficiency among adults, including pregnant women, using a semi-probabilistic approach. The concentration of iodine in the sampled salts decreased by 57% from the production site to the consumers. The assessment of exposure showed that adults in 63% (n=20) of the households, including 90% (n=29) with pregnant women, were at risk of insufficient iodine intake. A monitoring and evaluation system needs to be established to ensure adequate supply of iodine along the distribution chain. Special attention is needed for the retailers and consumers. At these levels, dissemination of information regarding proper storage and handling of iodized salt is necessary to address the reported loss of iodine from salt. Key words: Cross-sectional studies; Iodine; Iodine deficiency; Salt; Ethiopia DOI: 10.3329/jhpn.v28i3.5550 J HEALTH POPUL NUTR 2010 Jun;28(3):238-244